ONE-POT BIOFUELS PRODUCTION FROM WET MICROALGAE CHLORELLA VULGARIS IN SUPERCRITICAL METHANOL WITH HETEROGENEOUS CATALYSTS - HAN , FON YEE (2019)
Microalgae is a promising feedstock to produce biofuel. Due to its aquatic production environment, however, it requires complete dewatering of the system which consumes energy intensively before lipid extraction and conversion processes